Identification of mosquito species - Vasquez Christodoulou, Marlen (My University, 2026)
Dr. Margaret Wirth (University of Riverside, California) and Dr. Anna Samanidou (National School of Public Health) ▪ Identification of mosquito species ▪ Insecticide resistance evaluation to Culex spp.